The answer is 8
Here's why:
![{ ( \frac{( {6}^{7}) \times ( {3}^{3}) }{( {6}^{6}) \times ( {3}^{4} ) } )}^{3} = \\ ( \frac{6}{3} ) ^{3} = \\ \frac{216}{27} = 8](https://tex.z-dn.net/?f=%20%7B%20%28%20%5Cfrac%7B%28%20%7B6%7D%5E%7B7%7D%29%20%5Ctimes%20%28%20%7B3%7D%5E%7B3%7D%29%20%20%7D%7B%28%20%20%7B6%7D%5E%7B6%7D%29%20%5Ctimes%20%28%20%7B3%7D%5E%7B4%7D%20%20%29%20%7D%20%29%7D%5E%7B3%7D%20%20%3D%20%20%20%5C%5C%20%28%20%5Cfrac%7B6%7D%7B3%7D%20%29%20%5E%7B3%7D%20%20%3D%20%20%5C%5C%20%5Cfrac%7B216%7D%7B27%7D%20%20%3D%208)
The exponents are subtracted one from another when divided.
![\frac{ a ^{b} }{ {a}^{c} } = {a}^{b - c}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20a%20%5E%7Bb%7D%20%7D%7B%20%7Ba%7D%5E%7Bc%7D%20%7D%20%3D%20%20%7Ba%7D%5E%7Bb%20-%20c%7D%20)
We can look at the problem this way:
![( \frac{6^{7} }{6 ^{6} } \times \frac{3^{3} }{ {3}^{4} } ) = (6^{7 - 6} \times {3}^{3 - 4} ) = \\ ({6}^{1} \times {3}^{ - 1} )](https://tex.z-dn.net/?f=%28%20%5Cfrac%7B6%5E%7B7%7D%20%7D%7B6%20%5E%7B6%7D%20%7D%20%20%5Ctimes%20%20%5Cfrac%7B3%5E%7B3%7D%20%7D%7B%20%7B3%7D%5E%7B4%7D%20%7D%20%29%20%3D%20%286%5E%7B7%20-%206%7D%20%20%5Ctimes%20%20%7B3%7D%5E%7B3%20-%204%7D%20%29%20%3D%20%20%5C%5C%20%28%7B6%7D%5E%7B1%7D%20%20%5Ctimes%20%20%7B3%7D%5E%7B%20-%201%7D%20%29)
Since we have the power of -1 on the 3, we apply this rule:
![{a}^{ - b} = \frac{1}{ {a}^{b} }](https://tex.z-dn.net/?f=%20%7Ba%7D%5E%7B%20-%20b%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B%20%7Ba%7D%5E%7Bb%7D%20%7D%20)
Also this rule because we have the power of 1 on the 6:
![{a}^{1} = a](https://tex.z-dn.net/?f=%20%7Ba%7D%5E%7B1%7D%20%20%3D%20a)
Then we get this:
![(6 \times \frac{1}{3} )^{3} = ( \frac{6}{3} )^{3}](https://tex.z-dn.net/?f=%286%20%5Ctimes%20%20%5Cfrac%7B1%7D%7B3%7D%20%29%5E%7B3%7D%20%20%3D%20%28%20%5Cfrac%7B6%7D%7B3%7D%20%29%5E%7B3%7D%20)
We apply the rule:
![( \frac{a}{b}) ^{c} = \frac{ {a}^{c} }{ {b}^{c} }](https://tex.z-dn.net/?f=%28%20%5Cfrac%7Ba%7D%7Bb%7D%29%20%5E%7Bc%7D%20%20%20%3D%20%20%5Cfrac%7B%20%7Ba%7D%5E%7Bc%7D%20%7D%7B%20%7Bb%7D%5E%7Bc%7D%20%7D%20)
We get this:
Answer:
Step-by-step explanation:
Hope you won't be turned off by a correction, but we really need to use the symbol " ^ " to denote exponentiation.
Thus, we have x^2 = 100
Taking the square root of both sides, we get x = plus or minus 10. Verify, please, that both x = -10 and x = +10 satisfy the given equation.
It is 36%, because a percent is defined as a part to a whole, so in this scenario the part is the number of votes for maria and the whole is the number of kids in the class, so if we put it into fraction form we'll 9/25, which can be increased to 36/100 or you can input it into a calculator and convert to percent form